The Students` Perception in Arranging Discourse Units and Text Structure in Writing Narrative Text - Nurhayati, Dwi Astuti Wahyu (Indonesian Journal of EFL and Linguistics, 2024)
This article deals with the arrangement of discourse, namely cohesive devices and structure of text in narrative text writing. The students` perspective is also discussed in the indicated investigation. The objectives are to capture the pupils `point of view in arranging discourse units and constructing text structure in writing. The data were taken from fourth-semester students` narrative text writing at UIN SATU Tulungagung, and interview results were analyzed. There are twelve texts analyzed in this study. This study was conducted using a descriptive method with a qualitative approach. The findings show that there are misuses in applying linguistics tending to unite instruments, including allusion, replacement, and omission of parts of a word or sentence, as well as combination. Then, some lexical cohesive devices are easier to understand than grammatical ones, especially repetition, hyponyms, and meronyms. However, students are confused about using synonyms and antonyms collectively. The implementation of narrative text structure was also achieved. In addition, from students` point of view, the elements of cohesive devices need to be studied further as a lack of understanding of the devices affects their writing skills.